Institutional Determinants of Higher Education Students’ International Mobility within the Erasmus Programme Countries - Bartha, Zoltán; S. Gubik, Andrea (Theory, Methodology, Practice – Review of Business and Management, 2018)
One of the major EU policy objectives is to enhance the international mobility of students. The Leuven Communiqué published in 2009 set an objective of increasing the ratio of European Higher Education Area (EHEA) higher education graduates participating in a study or a training period abroad to at least 20% by 2020. However, currently the majority of European Union Member States perform significantly below the target in this respect. Also, since a low number of students are interested in mobility programmes, the funds of the Erasmus-type student mobility programs remain unused. This study focuses on highlighting the factors that represent barriers to student participation in mobility programs. After conducting a literature review on international student mobility and presenting major statistics describing outbound mobility, this study investigates factors related to institutional components of the higher education system that affect the international mobility of Erasmus young people. Among the explanatory factors related to Erasmus-type student mobility, cultural factors including Hofstede’s indulgence and uncertainty avoidance seem to have the greatest influence on student mobility intentions in Europe. The findings revealed that better planned Erasmus processes (pre-, during and postmobility activities such as departure, course choice, staying in a host country, etc.) and better communicated career opportunities and labour market values of the mobility could considerably contribute to an increase in the number of outbound students. One of the main lessons learned from the conducted analyses is that Europe’s rich cultural diversity needs to be considered in the course of promoting the Erasmus Programme in Europe. In addition to adopting common communication, promotion and direction strategies, programmes need to be elaborated that take national specificities into account.